Identification of Plasmodium Falciparum Merozoit Surface Protein-1 (PFMSP-1) Gene From Malaria Patients in Hanura Area, Lampung, Indonesia - Ade Triajayanti; Jhons Fatriyadi Suwandi; Betta Kurniawan; Nurul Utami (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Introduction: Malaria is a major health problem not only in Indonesia, but also the world. Incidence of anti malarial drug resistance has been found, and one of the possible cause is genetic factors. The changes that occur in the Plasmodium falciparum gene cause genetic variations that lead to resistance for treatment. There is a gene with high polymorphism that can be used as a gene marker of genetic variation in Plasmodium falciparum. Aim of Study: This study aim to identification of plasmodium falciparum merozoit surface protein-1 (PFMSP-1) gene from malaria patients in Puskesmas Hanura, Pesawaran, Lampung. Methods: Descriptive method with morbidity survey approach is used in this study. There are total 23 biological material stored that had been taken in 2016 from malaria patient in Puskesmas Hanura, Pesawaran, Lampung, by consecutive sampling. Identification of genetic variance of the Plasmodium falciparum gene was performed by nested PCR at Medical Faculty Biomolecular Laboratory of Lampung University. The results of this study were processed using a computer software. Results: There are 23 samples that amplified following nested PCR for Plasmodium falciparum Merozoit Surface Protein-1 (PFMSP-1) gene target. In all samples studied, there are PFMSP-1 gene with six variations base pair length range from 200 to 2000 bp. Conclusions: this study has successfully amplified PFMSP-1 gene from individual’s blood sample infected by Malaria in Puskesmas Hanura work region, Pesawaran, Lampung.